Interim Report of the Special Rapporteur on Freedom of Religion or Belief: Indigenous Peoples and the Right to Freedom of Religion or Belief - Shaheed, Ahmed (Journal of the Council for Research on Religion, 2024)
In the present report, the Special Rapporteur on freedom of religion or belief, Ahmed Shaheed, initiates a critical conversation within the United Nations system and beyond on obstacles and opportunities facing indigenous peoples’ freedom of religion or belief – a largely overlooked subject. Understanding indigenous peoples and their diverse religions or beliefs is impossible without acknowledging historical and ongoing experiences of discrimination, violence and hostility, which threaten their spiritual, cultural and physical survival. The Special Rapporteur explores “indigenous spirituality” as a typically nature-based “way of life”, documents experiences of affected rights holders – from forced displacement to environmental destruction – and provides recommendations to protect and promote the freedom of religion or belief of indigenous peoples, consistent with international law.